LACUNARITY AS INDEX OF EVALUATION OF WIND DIRECTION IN PERNAMBUCO - LUCENA, Leandro Ricardo Rodrigues de; CUNHA FILHO, Moacyr (Brazilian Journal of Biometrics, 2019)
Wind direction data were recorded from January 2008 to February 2011, at nine weather stations (Recife, Caruaru, Arcoverde, Garanhuns, Surubim, Floresta, Ibimirim, Serra Talhada and, Cabrobó), in the state of Pernambuco, Brazil, operated by the Instituto Nacional de Meteorology (INMET). Lacunarity analysis was performed in order to evaluate wind direction on those weather stations. In Recife the predominance of the wind was in the east (E)-southeast (SE) direction. In the agreste of the state of Pernambuco the predominant direction of the wind is the same one of Recife. In the Sertão of Pernambuco the wind predominates in the east (E)-sul (S) direction. Small values of lacunarity are caused by the presence of local winds, while large values of lacunarity are caused by lack of wind in a certain direction.